Magazine Teaching Materials as an Effort to Increase Students' Interest in Learning - Maulida Mawaddatul Husnah; Anak Agung Gede Agung (Jurnal Edutech Undiksha, 2023)
The lack of variation in the use of teaching materials in learning impacts students' interests and academic results. The purpose of this study is to develop magazine teaching materials as well as present the results of validating magazine teaching materials in Mathematics subjects which have the potential to foster student interest in learning. This type of research is development research with the ADDIE model. The subjects of this development research were one subject matter expert; 1 learning media expert; 1 learning design expert; 3 individual trial students; 6 students in small group trials. Data was collected by observation, document study, interviews, and questionnaires. The data collection instrument used was a questionnaire. The data analysis used is descriptive qualitative and descriptive quantitative. The research results, magazine teaching materials, were declared valid from the subject content experts' review showing that magazine teaching materials had a good predicate with a result of 80.00%. The review results by learning design experts show that magazine teaching materials have a very good rating, with a result of 91.00%. The review results by learning media experts show that magazine teaching materials have a very good rating, 92.00%. The results of individual trial reviews have a very good rating, with a result of 99.09%. The results of the small group trial had a very good rating with a yield of 98.18%. It was concluded that magazine teaching materials in Mathematics are valid and appropriate for learning.